Barriers and facilitators to students with physical disabilities' participation in academic laboratory spaces. - Jeannis, H.; Goldberg, M.; Seelman, K.; Schmeler, M.; Cooper, R. A. (Disability & Rehabilitation: Assistive Technology, 2020)
Purpose: To provide empirical evidence on learning barriers and facilitators in instructional science and engineering laboratory settings from a national survey on students with physical disabilities (SwD-P). Methods: A nationwide self-report survey, the Full Participation Science and Engineering Accessibility (FPSEA), was disseminated online via Qualtrics. Approximately 1200 organizations and universities across the United States were contacted through purposive sampling. Descriptive statistics were primarily used for the analysis of the results. Results: Survey findings reveal that students experience a wide range of limitations to full participation in the laboratory, from entering the laboratory (25%) to being given passive roles (50%). Additionally, while 66% of respondents indicated that instructors were willing to help SwD-P participate in science and engineering (S&E) laboratories, 16.8% were not willing to do so, and 47% SwD-P felt that practices were not in place to provide accommodations. The survey also reveals a range of facilitators such as elevators, ramps, accessible course materials and peer assistance. Most respondents (74%) also indicated that peers were helpful in completing laboratory tasks. Conclusion: This survey provides empirical evidence that was previously voiced through non-empirical information in the literature. Participants cited barriers such as inappropriate accommodations and instructors' negative viewpoints, as well as gaining access to facilities even after the enactment of the Americans with Disabilities Act (ADA). These findings suggest that while ADA has lessened some barriers to SwD-P, barriers remain in using the laboratory space. The FPSEA survey fills the gap in finding barriers and facilitators to using S&E laboratories from the SwD-P's perspective. Barriers students with disabilities encounter in science and engineering (S&E) laboratory environments remain unclear. The FPSEA survey fills the gap in finding barriers and facilitators to using S&E laboratories from the SwD-P's perspective. The FPSEA survey allows former and current SwD-P to share their experiences using a postsecondary S&E instructional laboratory.